Policy analysis of the mbg program from the perspective of food security and nutrition for school children case study at senior high school 1 Pandeglang - Hasyim Adnan (Journal of Law Science, 2026)
The Free Nutritious Meal Program (MBG) is one of the government's strategic policies to improve the quality of human resources by fulfilling students' nutritional needs. This study aims to analyze the implementation of the MBG Program policy from the perspective of food security and nutrition for school children at Senior high school 1 Pandeglang. The research focuses on the effectiveness of program implementation, its contribution to fulfilling students' nutritional needs, and its impact on food security in the school environment. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Research informants consisted of school officials, students, program implementers, and parents. The results show that the implementation of the MBG Program at Senior high school 1 Pandeglang has a positive impact on improving students' nutritional intake, improving learning concentration, and reducing unhealthy food consumption habits in the school environment. This program also supports food security efforts by providing affordable and sustainable nutritious food for students. However, the program implementation still faces several obstacles, such as budget limitations, menu variations, and suboptimal monitoring of food nutritional quality. Therefore, synergy between the government, schools, and the community is needed to increase the effectiveness of MBG policies so that the goal of improving the quality of student health and education can be optimally achieved. This research is expected to serve as a reference in developing food and nutrition policies for school children in Indonesia.